2014
DOI: 10.1002/car.2327
|View full text |Cite
|
Sign up to set email alerts
|

Filicide and Parental Separation and Divorce

Abstract: This paper discusses the findings of a ten‐year study of filicide in Victoria, Australia, using the data from selected case files held in the Victorian coroner's office for the period 2000–09. The study sought to examine whether separation is a factor in filicide cases, as well as the role of other factors, such as domestic violence and mental illness. Also, the study sought to identify whether filicide perpetrators had contact with support services, including family and friends, general practitioners, mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
(18 reference statements)
0
21
0
6
Order By: Relevance
“…This form of child maltreatment can compromise child development directly, via the traumatic impacts of exposure to DV, as well as indirectly, by negatively impacting mothers' parenting and the co‐parenting relationship (Evans et al, ; Levendosky and Graham‐Bermann, ). For children of parents who separate, the negative impact of a domestically violent father can extend post‐separation: a long history of research has demonstrated that in the post‐separation period, mothers and children are at risk for continued and/or increasing violence at the hands of abusive ex‐partners/fathers (Brown et al, ; Hotton, ).…”
mentioning
confidence: 99%
“…This form of child maltreatment can compromise child development directly, via the traumatic impacts of exposure to DV, as well as indirectly, by negatively impacting mothers' parenting and the co‐parenting relationship (Evans et al, ; Levendosky and Graham‐Bermann, ). For children of parents who separate, the negative impact of a domestically violent father can extend post‐separation: a long history of research has demonstrated that in the post‐separation period, mothers and children are at risk for continued and/or increasing violence at the hands of abusive ex‐partners/fathers (Brown et al, ; Hotton, ).…”
mentioning
confidence: 99%
“…Holt's findings highlight how ongoing contact between fathers and children following separation can facilitate ongoing domestic violence and can be used by abusive fathers to continue to exert control over their ex‐partners, and the distress and sense of powerlessness felt by children caught in the middle of this. At its extreme, the ongoing control exerted by fathers post‐separation may rarely result in filicide, an issue explored previously in our themed issue on filicide (Brown et al ., ; Jaffe et al ., ; Sachmann and Harris Johnson, ). Nevertheless, the fathers themselves often reported a deep sense of loss.…”
mentioning
confidence: 77%
“…The conference's 34 papers covered a diversity of perspectives and a number of these perspectives are represented in this themed issue. One paper, from Thea Brown, Danielle Tyson and Paula Fernandez Arias (), picks up a dominant strand of the conference, namely, recent incidence studies. Such studies covered large numbers of deaths and examined the deaths retrospectively using reliable sources, such as coroners' offices.…”
Section: Proposed Extension Of the Filicide And Fatal Maltreatment Modelmentioning
confidence: 99%